Persepsi Wisatawan Milenial dan Generasi Z Mengenai Kegiatan Konservasi Lingkungan Saat Berwisata: (Studi Kasus di Desa Wisata Candirejo, Kabupaten Magelang) - Ahmad Abdul Aziz; Hardiman Hardiman; Arina Nindyar; Rayhan Alfiano S. P; Bunga Mirza S (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the perceptions of millennial and generation z tourists regarding the implementation of conservative and environmentally friendly tourism concepts in Candirejo tourism village, Kabupaten Magelang. This study uses a qualitative approach with a case study design. Data collection techniques uses semi-structured interviews and direct observation in Candirejo tourism village. This research informant consist of 6 peoples, consisting of 3 millennial tourists and 3 generation z tourists who have experienced tourism activities in Candirejo tourism village. Data analysis technique was carried out using thematic analysis methods. The results of the study indicate that conservation and environmentally friendly practices carried out by the tourism village managers and tour operators are able to provide a positive impression for millennial and generation z tourists. This study concludes that both millennial and generation z tourists consider the conservation and environmentally friendly concepts implemented in the Candirejo tourism village to be an added-value in increasing interest in traveling to the destination because it can provide a new atmosphere and experience in carrying out tourism activities.